Continuity of care in youth services: A systematic review. (April 2017) - Naert, Jan; Roose, Rudi; Rapp, Richard C.; Vanderplasschen, Wouter
Abstract: Improving continuity of care is an important objective of various interventions and innovative programs for youngsters in vulnerable situations. Yet, the definition and conceptualization of continuity of youth care remains unclear, as well as important benefits and pitfalls regarding its implementation. Therefore, this study provides a systematic review of the literature, focusing on the conceptualization and evaluation of continuity. Database searches revealed 28 studies that focus on youth care interventions aimed at improving continuity of care. Selected studies were analyzed in Nvivo, using a three dimension model of continuity of care developed in general practice. Results show that continuity of care is rarely the central focus in youth services research. Moreover, its conceptualization is often limited to management aspects of continuity rather than highlighting other dimensions of continuity (e.g., relational and informational continuity). Also, experienced continuity of care as perceived by youngsters themselves is underrepresented in the selected studies, resulting in a partial view on continuity in youth care. It is concluded that more research is needed on youngsters' perceptions of continuity of youth services and its relational and information aspects, using qualitative study designs. Highlights: A small number of studies have focused on continuity of youth care as central research theme. Management continuity is the most frequently studied dimension of continuity in youth care research. More attention is needed for youngsters voices in research on continuity in youth services.